Costing Household Surveys for Monitoring Progress Toward Ending Extreme Poverty and Boosting Shared Prosperity - Kilic, Talip; Serajuddin, Umar; Uematsu, Hiroki; Yoshida, Nobuo (World Bank, Washington, DC, 2017)
On October 15, 2015, World Bank Group President Jim Yong Kim announced the World Bank Group’s commitment to support the 78 poorest countries to implement a multi-topic household survey every three years between 2016 and 2030, for monitoring progress toward ending extreme poverty and boosting shared prosperity. This paper estimates the resource requirements to achieve the objectives of implementing 390 surveys across 78 International Development Association countries from 2016 to 2030, and providing direct technical assistance to the national statistical offices on all facets of survey design, implementation, and dissemination toward timely production of quality household survey data. The approach to the costing exercise is unique, as it makes use of detailed data on actual survey implementation and technical assistance costs from a group of countries, unlike previous attempts at costing household survey data gaps. The required total budget, in accordance with the survey design features recommended by the World Bank Household Survey Strategy, is estimated at US$945 million for the period of 2016-2030. Of this, US$692 million is projected to cover the survey implementation costs across 78 countries, and US$253 million is projected to cover the costs of direct technical assistance to be provided to the national statistical offices.